1985
DOI: 10.1111/j.1745-4603.1985.tb00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Mechanical Properties, Composition and Perceived Texture of Beefburgers

Abstract: Twenty‐five brands of beefburgers were bought at retail in the United Kingdom, and their weights and dimensions, chemical composition, compressive strength and expressible fluid measured before and after grilling and compared with sensory evaluations. Compressive strength of grilled burgers measured with a punch and die, averaged 2.6 × 104 Nm−2 and varied from 1.1 to 4.6 × 104Nm−2 between brands. Beefburgers with a more rubbery, cohesive and coarser, tougher texture had higher compressive strength, higher tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Objective chewiness (the total work required) correlated well with all attributes except initial juiciness, ease of swallow, residual, toothpack, and mouth-coating. Rhodes et al (1972) and Jones et al (1985) found that single measures or combinations of different objective parameters did not improve the correlations for sensory texture responses over those already reported in the literature with various objective measuring devices. The sensory profile encompasses more aspects of meat texture than the objective profile.…”
Section: Objective and Sensory Texture Relationshipsmentioning
confidence: 47%
“…Objective chewiness (the total work required) correlated well with all attributes except initial juiciness, ease of swallow, residual, toothpack, and mouth-coating. Rhodes et al (1972) and Jones et al (1985) found that single measures or combinations of different objective parameters did not improve the correlations for sensory texture responses over those already reported in the literature with various objective measuring devices. The sensory profile encompasses more aspects of meat texture than the objective profile.…”
Section: Objective and Sensory Texture Relationshipsmentioning
confidence: 47%
“…The statistical technique (PCA) can also be used to study relationships between sensory properties and objective measurements. Jones et al (1985) used PCA to find the correlation between mechanical properties, composition and perceived texture of beefburgers. Martens (1986) studied the correlation of sensory and chemical quality criteria of stored vs nonstored frozen peas by multivariate data analysis, while Resurrection and Shewfelt (1985) studied the relationships between sensory attributes and objective measurements of post-harvest quality of tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…There are some factors that account for poor correlation between instrumental textural parameters and sensory textural attributes. The major one is the different process of measurement between the two systems (Voisey and Larmond 1977;Jones et al 1985;Hutchmgs and Lillford 1988). The sensory process is dynamic with varying force, varying deformation and varying food status while the instrumental process is static or at best semi-dynamic with constant variables.…”
Section: Correlationsmentioning
confidence: 99%
“…1985) could improve the correlation remains to be studied. Combinations of the instrumental measures (Jones et al 1985) or multi-regression analysis are also recommended for future correlation study.…”
Section: Correlationsmentioning
confidence: 99%
See 1 more Smart Citation